2017
DOI: 10.1016/j.ghir.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal growth and bone mineral acquisition in type 1 diabetic children; abnormalities of the GH/IGF-1 axis

Abstract: Type 1 Diabetes Mellitus (T1DM) is one of the most common chronic diseases diagnosed in childhood. Childhood and adolescent years are also the most important period for growth in height and acquisition of skeletal bone mineral density (BMD). The growth hormone (GH)/insulin like growth factor -1 (IGF-1) axis which regulates growth, is affected by T1DM, with studies showing increased GH and decreased IGF-1 levels in children with T1DM. There is conflicting data as to whether adolescents with TIDM are able to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 127 publications
2
46
0
5
Order By: Relevance
“…Aşırı kilolu ve Tip 1 DM'li hastalarda kan leptin miktarını araştıran bir çalışmada DM'li grupta leptin ifadesinin anlamlı bir şekilde düştüğü saptanmıştır (25). Bu konuda yapılan çalışmaların bazısı Tip 1 DM durumunda leptin ifadesinin değişmediğini (26), bazısı ise arttığını göstermiştir (27)(28)(29).…”
Section: Discussionunclassified
“…Aşırı kilolu ve Tip 1 DM'li hastalarda kan leptin miktarını araştıran bir çalışmada DM'li grupta leptin ifadesinin anlamlı bir şekilde düştüğü saptanmıştır (25). Bu konuda yapılan çalışmaların bazısı Tip 1 DM durumunda leptin ifadesinin değişmediğini (26), bazısı ise arttığını göstermiştir (27)(28)(29).…”
Section: Discussionunclassified
“…Відомо, що хронічна гіперглікемія викликає пригнічення остеобластів, а також неферментативне глікування білків, що в подальшому веде до порушення їх функції [6,7].…”
Section: вступunclassified
“…Studies have shown low IGF-1 in patients with T1D, which could indirectly affect bone turnover. (13)(14)(15) With impaired endogenous secretion, portal levels of insulin are low in T1D whereas the exogenous insulin results in peripheral hyperinsulinemia. A consequence is that, despite adequate dose of insulin to normalize blood glucose, this does not result in an increase in IGF-1.…”
Section: Introductionmentioning
confidence: 99%